Knowledge about STD/AIDS and sexual behavior among high school students in Rio de Janeiro, Brazil - Anete Trajman; Márcia Teresa Belo; Eleny G. Teixeira; Vicente C. S. Dantas; Frederico M. Salomão; Antônio J. Ledo A. Cunha
The incidence of AIDS and other sexually transmitted diseases (STDs) is increasing among adolescents. In order to better understand high-risk sexual behavior among students, a cross-sectional study based on a self-answered anonymous questionnaire was conducted in 10 public and private high schools in Rio de Janeiro, Brazil. Data were obtained on sociodemographics, knowledge of STD/AIDS, and sexual behavior. Among 945 students aged 13-21, 59% were sexually initiated, and the median age at first sexual intercourse was 15 years (range: 7-19). Although 94% reported being aware of the need for condom use for protection, only 34% informed always using condoms during sex. Low family income was associated with unsatisfactory knowledge (OR = 9.40; 95% CI = 6.05-14.60) and inconsistent condom use (OR = 11.60; 95% CI = 5.54-24.30). However, unsatisfactory knowledge was not associated with inconsistent condom use. School-based educational programs should focus on sexual behavior more than on transmission of knowledge, as well as targeting low-income students.